Surveillance, counter-terrorism and comparative constitutionalism - Davis, Fergal Francis; McGarrity, Nicola; Williams, George, 1969- (Abingdon, Oxon : Routledge, 2014)
'The decade after the September 11, 2001 terrorist attacks saw the enactment of anti-terrorism laws around the world that challenged understandings and assumptions about public institutions, human rights and constitutional law. Many of those laws remain on the statute books and continue to have a profound impact on constitutionalism and the rule of law. One of the most striking and rapid areas of development has been the conferral of increased powers of surveillance on law enforcement and intelligence agencies. The chapters in this edited book examine the impact of these powers on constitutionalism at both the domestic and international levels. The book discusses the prevalence of mechanisms of mass surveillance; the challenges that technological developments pose for constitutionalism; new actors in the surveillance state; the use of surveillance material as evidence in court and the difficulties of balancing secrecy and fair trial requirements; and the effectiveness of constitutional and other forms of review of surveillance powers. The contributors to the book who are leading international experts in anti-terrorism and constitutional law take a comparative approach looking at jurisdictions including the United States, Canada, United Kingdom, Europe, Israel, India, Japan, China and Australia. The book draws important conclusions about the constitutional implications, short- and long-term, domestic and international, of the expansion of surveillance powers after 9/11'--
Mapping the terrain / Fergal Davis, Nicola McGarrity and George Williams -- A judicial perspective : surveillance evidence and the right to a fair trial / Anthony Whealy QC -- Championing local surveillance in counter-terrorism / Clive Walker -- Surveillance regimes in contemporary India / Ujjwal Singh -- Privatized counter-terrorist surveillance : constitutionalism undermined / Fiona de Londras -- How secure is our privacy in seceurope? European security through surveillance / Monica Den Boer and Flora Goudappel -- Preserving privacy in a digital age : lessons of comparative constitutionalism / David Cole -- On the end of freedom in public spaces : legal challenges of wide-area and multiple-sensor surveillance systems / Jens Kremer -- GPS surveillance and human rights review : the European Court of Human Rights and the United States Supreme Court in comparative perspective / Federico Fabbrini and Mathias Vermeulen -- The impact of human rights law on measure of mass surveillance in the United Kingdom / Merris Amos -- Transatlantic perspectives on counter-terrorism surveillance : surveillance, borders and the culture of legality / Cian C. Murphy -- From the west to the east : migration of surveillance policy / Akiko Ejima -- Warrantless wiretrapping in the United States / Owen Fiss -- From convert to coercive : a new model of surveillance by intelligence agencies / Nicola McGarrity and George Williams -- The use of intelligence in counter-terrorism prosecutions and the role of the prosecutor / David Scharia -- State surveillance in an age of security / Conor Gearty -- Politicized challenges, depoliticized responses : political monitoring in China's transitions / Hualing Fu -- Internet surveillance and popular constitutionalism / Vanessa MacDonnell.
Includes bibliographical references and index.
Keywords: Terrorism -- Prevention -- Law and legislation; Electronic surveillance -- Law and legislation